EVALUASI KEGIATAN SURVEILANS EPIDEMIOLOGI DI PELABUHAN DALAM UPAYA PENCEGAHAN WABAH FLU BURUNG (STUDI KASUS DI PELABUHAN MALUNDUNG KKP KELAS II TARAKAN) - jamaludin abduh al ghozali (The Indonesian Journal of Public Health, 2016)
Avian Influenza cases remains an international concern, including Indonesia after it was first discovered in China and spread to Indonesia and caused 165 deaths up to 2014. Avian Influenza cases was set to Extraordinary Events in Indonesia at that time. One of the agencies that perform basic tasks and functions of epidemiological surveillance to the risk of occurrence of Avian Influenza outbreak is Port Health Office Class II Tarakan. This study aimsto evaluate epidemiological surveillance operations of Avian Influenza outbreak risk at Foreign Ships in Port Health Office Class II Tarakan. This research was conducted descriptively with qualitative approach. Research variable included input (personnel, funds, data, methods, tools), process (data collection, data processing, analysis and interpretation of data) and output (report and dissemination of the report). From the research there were several indicators of sufficiency in conducting surveillance activities that were still less than the standard, such as personnel, tools, transportation, and communication. Surveillance officers are still less qualified, where many officers who are also tasked with other activities and only one officer who has attended the surveillance training. Vehicle also became one the factor that weren’t enough, while the process and output indicators has met the standard. The conclusion of this research is that the process and output of epidemiological surveillance activities in the Port Health Office Class II Tarakan has been going well and according to indicators, although there is a shortage on the input. It is recommended that Port Health Office Class II Tarakan need to recruit surveillance officers and give training to officers who have been there as well as the provision of transportation to anticipate input shortages in surveillance activities.Keywords:evaluation, epidemiological surveillance, avian influenza, port